An intelligent design for Ni-based superalloy based on machine learning and multi-objective optimization - Deng, Yuedan; Zhang, Yu; Gong, Xiufang; Hu, Wang; Wang, Yucheng; Liu, Ying; Lian, Lixian (Materials & design, 2022)
[Display omitted] •A prediction model of Multi-objective Evolutionary Algorithm combined with Machine Learning was established to optimize multiple properties simultaneously.•Ni-based superalloy candidates were obtained with high γ′ solves temperature, high γ′ volume fraction and low topologically closed-packed phase content.•Properties of Ni-based superalloy candidates verified by experiment showed great accuracy with prediction. The simultaneous consideration of multiple conflicting properties in alloy optimization design is necessary yet remains challenging. A comprehensive strategy of machine learning (ML) and multi-objective optimization based on thermodynamic simulation data was proposed to accelerate the composition design of Ni-based superalloys. The microscopic parameters were determined by Pearson correlation analysis and domain knowledge as the key affect factors of tensile strength and elongation. The Multi-objectives Evolutionary Algorithm (MOEA) was adopted to search the well-built surrogate by ML meta-heuristically for the Pareto front of three objectives and its responding Pareto optimal solution set of composition. Furthermore, nine high-performance superalloy samples selected from the obtained Pareto front were well verified by fabricating and testing in the laboratory. Specially, a new composition among the nine as-fabricated samples was the best one according to the pre-defined design preferences with the γ′ solvus temperature, γ′ volume fraction, and TCP phases content approximating to 1210 °C, 65%, and 0.01%, respectively. This intelligent cooperation strategy based on ML and MOEA extends the methodology for multi-composition and multi-property design materials, which can optimize multiple conflicting objectives simultaneously rather than do one by one.